(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Aim Aim of the present study was to identify the relationships between linear, angularkinematic parameters and slice service performance.Methods Five (N=5) male tennis players from Guru Nanak professional tennis academy Chandigarh withHeight176.58±4.52, Weight72.36±7.26, and Age22.30±1.52 were chosen for the study.Results linear kinematic variable’s (Centre of gravity) mean and SD reported was 117.52±10.46, whereasin case of angular kinematic variables, it is evident that Mean was maximum for Shoulder Joint angle(179.60) and minimum for Ankle Joint angle (135.20).Conclusion Based on the findings of the current empirical investigation, it is possible to draw theconclusion that a similar study can be carried out with a larger sample size and more experienced tennisplayers in terms of technical and performance ability